2011
DOI: 10.1002/jat.1731
|View full text |Cite
|
Sign up to set email alerts
|

Blood thioredoxin reductase activity, oxidative stress and hematological parameters in painters and battery workers: relationship with lead and cadmium levels in blood

Abstract: Oxidative stress has been shown to be involved in lead and cadmium toxicity. We recently showed that the activity of the antioxidant enzyme thioredoxin reductase (TrxR) is increased in the kidneys of lead-exposed rats. The present study evaluated the blood cadmium and blood lead levels (BLLs) and their relationship with hematological and oxidative stress parameters, including blood TrxR activity in 50 painters, 23 battery workers and 36 control subjects. Erythrocyte δ-aminolevulinate dehydratase (δ-ALA-D) acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 47 publications
(62 reference statements)
6
37
1
2
Order By: Relevance
“…In agreement with our results the study of Moro et al (2010) and Conterato et al (2013) reported an increased MDA level in painters occupationally exposed to paint thinners.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our results the study of Moro et al (2010) and Conterato et al (2013) reported an increased MDA level in painters occupationally exposed to paint thinners.…”
Section: Discussionsupporting
confidence: 93%
“…MDA is formed as its end product. Anti-oxidant enzymes are defense system against oxidative stress (Barrera 2012; Conterato et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies reported significantly higher levels of GPx activity in the lead-exposed groups than in the controls (Monteiro et al 1985 ;Solliway et al 1996 ;Oktem et al 2004 ;Kasperczyk et al 2004aKasperczyk et al , 2012Han et al 2005 ;Ergurhan-Ilhan et al 2008 ;Conterato et al 2013 ). Five studies reported lower GPx activity in the lead-exposed groups than in the control groups (Sugawara et al 1991 ;Chiba et al 1996 ;Wasowicz et al 2001 ;Kasperczyk et al 2009 ;Grover et al 2010 ), and two studies reported no signifi cant differences between GPx activity and BLL (Garçon et al 2007 ;Rendon-Ramirez et al 2014 ).…”
Section: Lead-induced Oxidative Stress In Occupationally Exposed Popumentioning
confidence: 87%
“…Among these, 15 studies reported a signifi cant positive correlation between BLLs and MDA concentrations ( r = 0.15-0.80; p < 0.05). Only one study did not fi nd signifi cant association between BLLs and MDA concentration ( Conterato et al 2013 ). Four studies reported that TBARS were detected measuring LPO in body fl uids.…”
Section: Lead-induced Oxidative Stress In Occupationally Exposed Popumentioning
confidence: 97%
See 1 more Smart Citation